20-ām nūṟṟāṇṭiṉ Tamiḻc ciṟukataiyāciriyarkaḷ (Kavita Papḷikēṣaṉ, 1999)
Brief biographies of 20th century Tamil short story writers; includes their selected writings
In Tamil
Keywords: Biografie; Authors; Tamil; Short stories; Tamil